Comfort and function remain key factors in upper limb prosthetic abandonment: findings of a scoping review - Smail, Lauren C; Neal, Chantelle; Wilkins, Courtney; Packham, Tara L (Disability and rehabilitation: Assistive technology, 2021)
Rates of prosthetic device abandonment are dramatically high; however, the reasons behind abandonment are less understood. A scoping review was conducted to explore the current state of the literature on why individuals abandon upper limb prosthetic devices and consider how these reasons have evolved historically. A systematic search of the literature identified 123 articles. After reviewing the articles using predetermined inclusion and exclusion criteria, nine relevant articles were included in the final review. The included articles covered passive, body-powered and myoelectric prosthetic devices. Across time, reasons for abandonment could be broadly categorized into comfort and function. Weight, temperature and perspiration were among the most common and persistent comfort-related reasons for abandonment. Regarding function, studies-reported abandonment was attributed to key concerns about control and sensory feedback, whereby participants may feel more functional without their device. In agreement with the previous literature, lack of comfort and function remain persistent reasons for upper limb prosthesis abandonment. Up-to-date research on reasons for abandonment of upper limb prosthetic devices is lacking, and recent prosthesis advancements have not been included in studies of device use, adoption and abandonment. Therefore, future work should explore reasons for abandonment in contemporary upper limb prosthetic devices. By understanding the reasons for prosthetic device abandonment, clinicians, therapists and researchers can use this information to proactively mitigate future upper limb prosthetic device abandonment. Findings from this review can be used to guide future prosthetic device development to improve these areas of concern and satisfy user needs.IMPLICATIONS FOR REHABILITATIONBy understanding the reasons for prosthetic device abandonment, clinicians, therapists and researchers can use this information to proactively mitigate future upper limb prosthetic device abandonment.The findings from this review can be used to guide future prosthetic device development to improve areas of concern and satisfy user needs.